A CHARACTERIZATION BETWEEN FIXED POINT PROPERTIES OF WEAK NONEXPANSIVE SEMIGROUPS AND THE EXISTENCE OF A LEFT INVARIANT MEAN ON THE SPACE OF WEAKLY ALMOST PERIODIC FUNCTIONS. (2017) - SOLIMAN, AHMED H.; BARAKAT, M. A.
No abstract available